Fighting Gender Inequality: Brazilian Feminist Movements and Judicialization as a Political Approach to Oppose Violence Against Women. (4th March 2018) - Elias, Maria Ligia Rodrigues; Machado, Isadora Vier
Abstract : How can oppressive structures be undermined in the pursuit of gender equality? Facing and combating violence against women is essential to reduce this inequality. This article explores the need for the judicialization of violence against women and gender inequality and the importance of the constitution of this process as a political arena in Latin America, especially in Brazil. In an unequal world, the juridical field, like many others, is characterized by complex social relations, and is therefore itself an object of dispute in the quest for greater freedom and autonomy for women. This article explores judicialization as one of the paths taken by Brazilian feminist movements as a way to combat violence against women. Feminism—both as a theory and as a political movement—is known to be manifold and heterogeneous. The judicialization of rights is one of many paths adopted in the bid to build a less unequal society. It is also important to note that the law has been used as an instrument of emancipation for various socially disadvantaged groups; it is not an exclusively feminist approach. This article analyzes the potentialities and limitations of judicialization as an instrument to combat gender-based inequality in Brazil.